(3HjGf cTa GdCdaGXs - (3TgGH GdOjf CMeO Hf eMeO Hf eMeO GdHLGFj , GdpqTngGH GdlCnqHPlj,J (B860 (3g` s
(3ChdgG (B:s
(3gPG HjGf cTa GdCdaGX dGHO ddabjg ef eYQaI GdCdaGX GdeSJYedI GdJi JLQi Ydi CdSfI GdabgGA ai Gdabg MJi dG jLQi ajg GdSgh hGdZdW s
(3BNQgG (B:s
(3Je HjGf cTa GdCdaGX HYhf Gddg Gdedc GdMaGX hGdMeO ddg hMOgq s
(3Vef eLehY , JQJjHgG (B: 1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B218 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B292s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3Gdabg GdESdGejs